The Influence of Financial Literacy, Lifestyle, and Consumer Behavior on Students' Financial Management - Meilanta Rantina (Universitas KH. Abdul Chalim Mojokerto, 2026)
Good financial management is a critical skill for students, who often face financial constraints yet are vulnerable to the pressures of lifestyle and consumptive behavior. This study aims to analyze the influence of financial literacy, lifestyle, and consumptive behavior on student financial management. This research uses a quantitative approach with a survey method. Data were collected through questionnaires distributed to students in the Management Department at UMCI, with a sample of 32 respondents selected using a sampling technique. Data analysis was performed using multiple linear regression analysis to test the relationships and influences between variables. The results show that financial literacy has a positive and significant influence on student financial management. Conversely, lifestyle and consumptive behavior were found to have a negative and significant influence on financial management. These findings indicate that students with a good understanding of finance tend to be able to manage their finances more effectively, while a hedonistic lifestyle and consumptive tendencies can disrupt financial planning and discipline. The implications of this study emphasize the need to increase financial literacy among students and to control lifestyle and consumptive behavior to support their financial well-being. This research is expected to provide input for educational institutions and students in designing educational programs and policies that support better financial management.